2019
DOI: 10.9734/jabb/2019/v21i430101
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Nutritional, Environmental Effects and Repressive Nature of Simple Sugars on the Production of endo-β-mannanase by Aspergillus flavus PT7 on Solid State Fermentation

Abstract: Aims:The importance of nutritional and environmental factors in the production of microbial enzymes cannot be overemphasized. Hence, endo-β-mannanase production was systematically studied in a step-wise approach of building up on the experimentally observed conditions favouring the production of this enzyme in Aspergillus flavus PT7. Place and Duration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Copra meal (CM) was the best by-product for mannanase production with an enzyme activity of 0.226 U/ml followed closely by palm kernel cake (PKC) at 0.207 U/ml. The proximate composition analysis of copra meal carried out by Antia et al [65] revealed that it has higher protein and moisture content than palm kernel cake (PKC) thus making it ideal for both fungal growth and mannanase production. Incubation time affects enzyme production significantly and it can vary from 24 h to 168 h depending on the microorganism and other culture conditions [66].…”
Section: Discussionmentioning
confidence: 99%
“…Copra meal (CM) was the best by-product for mannanase production with an enzyme activity of 0.226 U/ml followed closely by palm kernel cake (PKC) at 0.207 U/ml. The proximate composition analysis of copra meal carried out by Antia et al [65] revealed that it has higher protein and moisture content than palm kernel cake (PKC) thus making it ideal for both fungal growth and mannanase production. Incubation time affects enzyme production significantly and it can vary from 24 h to 168 h depending on the microorganism and other culture conditions [66].…”
Section: Discussionmentioning
confidence: 99%